Analysis Of Carrageenan Addition On Quality Of Spent Layer Hens Meatballs - Sari, Revita Putna; Anni, Faridah; Holinesti, Rahmi; Mustika, Sari (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
Spent laying hens are laying hens whose production period has expired but the meat of rejected laying hens can still be utilized by processing them into restructured meats. One of the products of restructured meats is meatballs. However, meatballs that come from rejected layers of chicken meat have a slightly tough texture. So it is necessary to add food ingredients that can improve the texture of meatballs, namely carrageenan. Carrageenan has good properties as a chewing agent because it can form a gel, so it can be used as an alternative additive in the manufacture of rejected laying hen meatballs. This study aims to analyze the quality of meatballs of dead laying hens with the addition of carrageenan as a thickening agent as much as 0%, 0.5%, 0.75%, and 1% in organoleptic tests on the quality of shape, color, aroma, texture, and taste. This research was conducted at the Culinary Workshop, Department of Family Welfare, Faculty of Tourism and Hospitality, Padang State University in August-September 2022. This type of research was a pure experiment with three repetitions and involving 3 expert panelists. The data obtained were then tabulated and continued to be tabulated and then continued with statistical analysis (ANOVA). If Fcount ≥ Ftable then continues with Duncan's test. The results showed that the addition of carrageenan affected the quality of the shape and texture of the meatballs of rejected laying hens. The more carrageenan used, the chewier the texture of the meatballs produced. The best quality results obtained after the study were found in treatment X3 with the addition of 1% carrageenan in the categories round shape (3.56), uniform shape (3.33), grayish-white color (3.33), fragrant aroma (3.33), 78), chewy texture (3.67), and savory taste (3.89).